(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Floor gymnastics is a part of the gymnastics group. Following the term floor, the gymnastics movements are performed on a mat or carpet. Front roll is a forward rolling movement over the back of the body (nape, back, piggag, back of the hip). The purpose of this study was to determine the effect of the student teams achievement division (STAD) learning model on the learning outcomes of front rolls in floor gymnastics learning for female students of class XII SMAN 2 Sumedang in the 2023 academic year. The research method used in this study is an experimental method using an instrument, namely a front roll. Data were taken from the initial test and the final test. The population of this study was all female students of class XII SMAN 2 Sumedang in the 2023 academic year, totalling 125 people, and the sample used was 25 female students of class XII SMAN 2 Sumedang. Based on the results of data processing, there were significant differences. This is indicated by the average value of the final test results achieved by the sample after receiving treatment, which is 75.64, where before receiving treatment, namely the initial test, the average value was 65.76. Meanwhile, regarding its significance, it can be seen from the increase test, which shows significant results at a real level of 0.05 with a degree of freedom of 10.3, namely t count> t table = 10.3> 1.711. So that the influence of the student teams’ achievement division (STAD) learning model on the learning outcomes of forward rolls in floor gymnastics learning is 15%.